The high Tafel slope and small potential dependence of activation energy for formic acid oxidation on a Pd electrode. (1st September 2018) - Uwitonze, Nestor; Zhou, Da; Lei, Jing; Chen, Wei; Zuo, Xia Qing; Cai, Jun; Chen, Yan-Xia
Abstract: Formic acid oxidation (FAO) on Pd electrode at various temperatures is investigated by cyclic voltammetry, potential step chronoamperometry and electrochemical in situ infrared spectroscopy (IRS). With increasing potential, FAO activity first increases, then decreases at higher potentials, the peak potential increases from 0.65 V to ca. 0.9–1.0 V with increasing temperature from 298 K to 343 K. The Tafel slope for FAO on Pd is found to be ca.260 ± 40mV/dec at around 0.25 V, it increases with the electrode potential and reaches ca. 470 ± 20 mV/dec at around 0.5 V. The apparent activation energies (Ea, app ) and pre-exponential factors (Aapp ) are estimated from the cyclic voltammograms or current transients recorded at different temperatures. Ea, app decreases slightly with increasing reaction potential from 0.25 V to ca. 0.6 V with a slope of ca. 0.27 eV/V. The H/D kinetic isotope effect is found to be ca. 2 in the potential region from 0.2 V to 0.4 V, it increases with potential at E > 0.4 V and reaches ca. 6 at 0.6 V. Only bridge-bonded bicarbonate and formate are detected by IRS during FAO on Pd, the role of these species for FAO on Pd are discussed. Possible origins for the large Tafel slope, and the correlation between the large Tafel slope and the small potential-dependent change of the activation energy are discussed.